Mobile Blogging as A Mean to Improve Journalism Education - Rozhkov, Alexandr; Bulatova, Madina; Noda, Larissa (International Journal of Interactive Mobile Technologies (iJIM), 2020)
On the basis of new experimental data, the present paper was aimed at analyzing the effectiveness of training journalism students through the use of blogs. This study included a field survey, during which the impressions of journalism students from the introduction of blogging in the educational process were analyzed. The examination involved 71 undergraduate journalism students of two Russian and two Kazakhstan universities. Innovative teaching strategies were introduced in the training process of mentioned institutions, and the corresponding methods of conducting specialized classes were developed. The experimental data confirmed several hypotheses related to the effectiveness of blogging in journalism education. The practical significance of the obtained results lies in the fact that the proposed approach allows the effective implementation of blogs in journalism training.